Defending against wireless network intrusion - Pathan, Al-Sakib Khan; Fadlullah, Zubair Md.; Fouda, Mostafa M.; Lee, Hae Young (Elsevier, 2013)
The security mechanisms for various wired networks are more or less well-defined. Especially when intrusion detection and prevention techniques are considered, wired networks appear to be in a much better status than their wireless counter-parts. Indeed, security concerns are, still, a significant impediment to widespread adoption of wireless network technologies. Because of the use of wireless communications technology, structure of the wireless networks, limited resources available on wireless devices, and open nature of wireless communications, employing an effective and efficient intrusion detection and prevention system for detecting and thwarting malicious attacks against wireless communications till remains a great challenge to researchers.